Efeito físico no solo através do uso de gado de corte em lavoura de soja - Moretti, Higor Kunz (My University, 2025)
Crop-livestock integration affects the soil in several ways, with increasing soil density, as well as compaction, there is also a decrease in porosity and soil moisture. In view of this information, the present work aimed to analyze the effect caused by trampping of Aberdeen Angus beef cattle in soil physical attributes, as well as the effect on soybean crop yield in the following summer. The study was carried out in three agricultural areas with different management of beef cattle, which included the following treatments: T0 (zero animals present), T1 (one bovine animal per hectare), T2 (two bovine animals per hectare). The experimental design used was completely randomized with 3 treatments and 5 replicates per treatment, randomly arranged in each of the treatments avoiding the paths used daily to search for water and shade. The variables evaluated are soil density, compaction through the use of the penetrometer, gravimetric and volumetric unit, total porosity and yield per hectare in soybean crop next summer. Data obtained were submitted to analysis of variance (ANOVA) and the media scans of the treatments will be performed by the Tukey test at 5% probability with the help of the agroestat statistical program, except for the yield per hectare that was used descriptive statistical analysis. Based on the results, it was concluded that: the use with animal load above one head per hectare directly affects soil density, causing an increase in compaction, ecrease of total pores and the moisture content of the available soil the plants consequently the yield of the crop with T0 with 2,100 kilograms per hectare, while the other treatments T1 and T2 with 1,800 and 1,380 kg per hectare respectively. [resumo fornecido pelo autor]
A integração lavoura-pecuária afeta o solo de diversas maneiras, com o aumento da densidade do solo, com a compactação e com a diminuição da porosidade e da umidade do solo. Diante dessas informações, o presente trabalho teve o objetivo de analisar o efeito causado pelo pisoteio dos animais bovinos de corte da raça Aberdeen Angus com peso medio de 450 quilogramas, em atributos físicos do solo e seu efeito sobre o rendimento da cultura da soja no verão seguinte. O estudo foi realizado em três áreas agrícolas com diferentes manejos de gado de corte, com os seguintes tratamentos: T0 (zero animal por hectare), T1 (um animal bovino por hectare), T2 (dois animais bovinos por hectare). O delineamento experimental utilizado foi inteiramente casualisado com três tratamentos e cinco repetições por tratamento, dispostos aleatóriamente em cada um dos tratamentos, evitando os trajetos utilizados diariamente pelos bovinos para a busca da água e sombra. As variáveis avaliadas foram a densidade do solo, a compactação através do uso do penetrômetro, a unidade gravimétrica e volumétrica, a porosidade total e o rendimento por hectare na cultura da soja no próximo verão. Os resultados mostraram que: o uso com carga animal acima de uma cabeça por hectare afeta diretamente a densidade do solo, ocasionando um aumento da compactação, a diminuição dos poros totais e o teor de umidade do solo disponível para as plantas. Em consequência disso, o rendimento da cultura de T0 foi de 2.100 quilogramas por hectare e de T1 e T2 foi de 1.800 e 1.380 quilogramas por hectare respectivamente. [resumo fornecido pelo autor]
Keywords: Agronomia; Solos - Densidade; Lavoura; Bovino de corte - Criação